Resíduos agroindustriais utilizados para produção de tanase por aspergillus sp isolado da caatinga do Nordeste Brasileiro - Nascimento, Katarina Botelho de Melo (2013)
The use of agro-industrial waste in the production of various bioproducts has emerged as a viable alternative for use in the formation of by-products through bioconversion of agro-industrial waste that are increasingly used. The waste material is characterized as highly heterogenous, and they serve both as a source of carbon and energy, as for microbial growth thus reducing the production costs of several microbial enzymes and minimizing the environmental impact that these materials would provoke to be disposed in the environment. Filamentous fungi has a high potential for biotechnological production of enzymes of microbial origin. The tanases are extracellular enzymes that catalyze the cleavage of hydrolyzable tannins, inducible produced by various microorganisms, mainly by filamentous fungi , for ferment solid, liquid or submerged in a wide application in various segments of origin industrial and commercial. This work presents a proposal to formulate considered economical means for tannase production using agroindustrial waste (coffee, grape and orange) by the filamentous fungus Aspergillus isolated from the caatinga of Pernambuco state. The first stage of the research consisted in the selection of the fungus, where he was active degrading tannic acid, but the strain that showed the best activity was the SIS 4. This strain was subsequently tested in culture media by adding 10 g/L of the agroindustrial waste salt solution containing 10 g /L tannic acid. The best results were obtained with the residue of coffee to the line previously selected.